Quality Characteristics of Salt Fortification with Dragon Fruit Peel in Plastic Packaging during Storage Period - Maflahah, Iffan; Asfan, Dian Farida (Department of Agro-industrial Technology, University of Brawijaya, 2020)
AbstractDragon fruit peel is another option for salt fortification beside of iodized salt. Dragon fruit peel contains source of vitamin C needed by our body. The objective of this study is to find out the quality characteristics of fortification of salt with dragon fruit peel during storage period. Fortified salt was stored in Low-Density Polyethylene (LDPE) and High-Density Polyethylene (HDPE) plastics at room temperature and at the temperature of 35°C. Fortified salt was stored for a month. Tests performed during storage period were water content, NaCl, vitamin A and vitamin C content. The experimental design used was randomized block design with 2 factors, those are temperature and packaging type. Statistic test was performed with Variance Test and Duncan Test in the significance level of 5%. Fortified salt production used 40% of dragon fruit peel extract. Results showed that different packaging type and storage temperature did not have real impact on NaCl and vitamin A content of fortification salt with dragon fruit peel. Water content of fortification of salt with dragon fruit peel is affected by storage temperature. However, packaging type does not give real impacts on vitamin A content. Packaging type have a real impact on vitamin C content. Fortification of salt with dragon fruit peel has the ability to bind vitamin C so that it can be used as an alternative source of vitamin C.Keywords: dragon fruit peel, salt fortification, storage